Analysis Of Agronomic Traits Combining Ability Of Sweetwaxy Double Recessive Corn Inbred Lines (Bangladesh Journal of Botany, 2023)
Sweet-waxy corn is a kind of fresh corn which is harvested, processed and eaten in the milk ripening period. It is one of the most popular special corns in the fresh corn market. In order to screen and evaluate the breeding value of sweet-waxy corn inbred lines, 10 selected sweet waxy double recessive corn inbred lines i.e JT111, JT113, JT116, JT120, JT124, JT128, JT131, JT135, JT139 and JT145 were used as female parents (P1), and 3 waxy corn inbred lines namely JN44, JN55 and JN88 were used as male parents (P2), and NC II design of incomplete diallel cross was used to analyze combining ability of 10 agronomic characters, including plant height, ear height, grain weight per ear, ear length, ear diameter, rows per ear, grains per row, 100-grain weight, skin residue rate and amylopectin content. Results showed that in general combining ability, JT124 had the best performance in ear length, grain number per row, 100-grain weight, skin residue rate and amylopectin content, and the better inbred lines were JT120, JT111 and JT113. In the special combining ability, JT124×JN55, JT124×JN88 and JT120×JN55 were the best crossing combinations. JT124, JT120, JT111 and JT113 could be used directly, and other inbred lines could be improved and reused. Plant height, row number per ear, grain number per row and 100-grain weight should be selected in early generation, while ear height, ear diameter, skin residue rate and amylopectin content should be selected in late generation. According to this, one can select the breeding target and the suitable parent inbred line.Bangladesh J. Bot. 51(4): 923-929, 2022 (December) Special